Canine mammary tumours: Size matters–a progression from low to highly malignant subtypes. (20th October 2020) - Gedon, Julia; Wehrend, Axel; Failing, Klaus; Kessler, Martin
Abstract: The purpose of this study was to evaluate a possible association between mammary tumour size and increasing degree of malignancy. Data of 625 dogs with a total of 1459 mammary tumours were analysed retrospectively. 80.3% dogs were intact, mean age at diagnosis was 9.7 ± 2.5 years, 75.8% were pure breed dogs. Median body weight was 20.0 kg. Malignant tumours (n = 580) were significantly larger than their benign counterparts (1.94 cm vs 0.90 cm in mean, respectively; P  ≤ .0001), resulting in a positive correlation between increasing tumour size and a change from benign to malignant ( P  ≤ .0001; rs  = 0.214). When malignant tumours were grouped into four degrees of increasing malignancy (complex/simple/solid/anaplastic carcinomas) a significant positive correlation between increasing tumour size and more malignant tumour degree ( P  ≤ .0001; rs  = 0.195) could be demonstrated. In a number of cases, highly malignant tumours were found to arise within less malignant lesions, supporting the concept of a further progression within the malignant tumour subtypes. In patients with multiple tumours, mean tumour sizes for malignant tumours were significantly smaller compared to patients with only one tumour (1.67 vs 2.71 cm in mean, respectively; P  < .0001). These findings suggest that mammary tumours progress not only from benign to malignant but also from low to highly malignant. An increase in diameter of only a few millimetres may therefore have a big impact on the patient's outcome.